The Effect of Dates Administration on Hemoglobin Levels in Pregnant Women Trimester III - Rahma Kusuma Dewi; Nara Lintan Mega Puspita; Huda Rohmawati; Siti Khotimah; Gina Salsabila (Journal of Global Research in Public Health, 2021)
Anemia in pregnancy is a condition of pregnant women with hemoglobin levels below 11 gr / % in TM I and III or <10.5 gr% in TM II. Herbal utilization is one of the alternative treatments non-pharmacology, one of which is the fruit dates. This study aims to determine the effect of giving dates on HB levels of pregnant women trimester III. The research design used is pre-experimental research. The population in this study is 16 people with total sampling techniques. The research instrument used SOP, haemometer, and observation sheet. The results of the study were analyzed using the Wilcoxon test. The Wilcoxon test results showed that there is no effect of giving dates to hemoglobin pressure levels in pregnant women trimester III in the community health center of Bangsongan Kediri in 2018. Based on the study results, it is expected that dates can be used as an alternative treatment for anemia in pregnant women.